2022
DOI: 10.1038/s43246-022-00310-x
|View full text |Cite
|
Sign up to set email alerts
|

Sub-volt switching of nanoscale voltage-controlled perpendicular magnetic tunnel junctions

Abstract: Magnetic random-access memory (MRAM) based on voltage-controlled magnetic anisotropy in magnetic tunnel junctions (MTJs) is a promising candidate for high-performance computing applications, due to its lower power consumption, higher bit density, and the ability to reduce the access transistor size when compared to conventional current-controlled spin-transfer torque MRAM. The key to realizing these advantages is to have a low MTJ switching voltage. Here, we report a perpendicular MTJ structure with a high vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 75 publications
0
28
0
Order By: Relevance
“…The relatively high power consumption of these mechanisms has created a need for novel low-dissipation alternatives such as voltage control of magnetism (VCM). It has been reported that applying voltage can lead to significant changes in magnetic properties including magnetic anisotropy, SOT efficiency, , and Curie temperature. , Furthermore, researchers have even realized voltage-controlled 180-degree magnetization switching in piezoelectric or multiferroic ferromagnetic devices where the time reversal symmetry is broken. , However, most of the current VCM efforts have been focused on ferromagnetic materials.…”
mentioning
confidence: 99%
“…The relatively high power consumption of these mechanisms has created a need for novel low-dissipation alternatives such as voltage control of magnetism (VCM). It has been reported that applying voltage can lead to significant changes in magnetic properties including magnetic anisotropy, SOT efficiency, , and Curie temperature. , Furthermore, researchers have even realized voltage-controlled 180-degree magnetization switching in piezoelectric or multiferroic ferromagnetic devices where the time reversal symmetry is broken. , However, most of the current VCM efforts have been focused on ferromagnetic materials.…”
mentioning
confidence: 99%
“…VCMA has been previously proposed as a writing mechanism for MRAM due to its potential high density and low power consumption, [53][54][55][56][57][58] where switching can be realized by tuning the width of a voltage pulse across the VC-MTJ. [53,56,58]- [71] On the other hand, Figure 1c depicts the writing operation principle for the VCMA-based reconfigurable PUF which is based on the idea of stochastic switching. At zero bias voltage, there are two minima in the energy landscape which are the two stable out-of-plane directions of the free layer magnetization.…”
Section: Device Structure and Operation Principlementioning
confidence: 99%
“…If the voltage is removed at half period, the magnetic moment will settle in the opposite direction. [53,56,[58][59][60][61][62][63][64][65][66][67][68][69][70][71] However, if the voltage is applied for a longer time, the precession will continue with a reducing amplitude due to damping, and the free layer will settle into an in-plane direction within a few nanoseconds. If the voltage pulse is removed at this point, the easy-axis is changed to perpendicular again and the magnetic moment reorients to one of the perpendicular states with equal probability.…”
Section: Device Structure and Operation Principlementioning
confidence: 99%
“…In precessional VCMA switching, the switching voltage, noted as V sw , is the value at which the energy barrier between the free layer states is eliminated. The switching voltage can be expressed as Vsw=tMgO0.33emtfree(Ki(V0.33em=0.33em0)/tfree2πMS2)/ξ,${V}_{sw} = {t}_{{\mathrm{MgO}}}\ {t}_{{\mathrm{free}}}( {{K}_i( {V\ = \ 0} )/{t}_{{\mathrm{free}}} - 2\pi {M}_{\mathrm{S}}^2} )/\xi ,$ [ 65,83,92 ] where t MgO is the thickness of the MgO tunnel barrier, t free is the thickness of the free layer, K i is the PMA, M S is the saturation magnetization, and ξ is the VCMA coefficient that quantifies the magnetic anisotropy's sensitivity to electric fields. As the switching voltage is inversely proportional to ξ , a sufficiently large VCMA coefficient is necessary for low write voltages and to achieve switching of nanoscale MTJs.…”
Section: Challenges and Research Opportunities For Vcma‐mrammentioning
confidence: 99%
“…On the other hand, a large enough energy barrier is needed to maintain sufficient thermal stability. The energy barrier can be written as Eb=0.33emπD2tfree(Ki(V0.33em=0.33em0)/tfree2πMS2)/4,${E}_{\mathrm{b}} = \ \pi {D}^2{t}_{{\mathrm{free}}}( {{K}_{\mathrm{i}}( {V\ = \ 0} )/{t}_{{\mathrm{free}}} - 2\pi {M}_S^2} )/4,$ [ 65,83,92 ] where D is the diameter of the device. For smaller devices, to have the same thermal stability coefficient Δ = E b / kT , a higher PMA is needed, imposing an even higher demand for the VCMA coefficient.…”
Section: Challenges and Research Opportunities For Vcma‐mrammentioning
confidence: 99%